Identifying the habitat quality of Scutellaria baicalensis based on baicalin content using the fuzzy matter element model. (August 2022) - Jiang, Yuan; Zhao, Zefang; Xiao, Yanqing; Xu, Hui
Graphical abstract: Highlights: Figuring out the baicalin content of wild Scutellaria baicalensis in China. Identifying the habitats of S. baicalensis by climate, soil and vegetation features. Dividing the habitats into four groups based on the baicalin content levels. Temperature related factors in habitat correlated closely to baicalin content. Fuzzy matter element model was evidenced effective for habitat grouping. Abstract: Plants form the basis of sophisticated traditional medicine systems, and information on the spatial distribution of high-quality medicinal herbs is a prerequisite and foundation for their effective utilization and conservation. Scutellaria baicalensis Georgi is a traditional Chinese medicinal plant, and baicalin is the main active ingredient of S. baicalensis. This research collected 470 samples of S. baicalensis through fieldwork and extracted baicalin content by high-performance liquid chromatography. We also collected 240 distribution sites from previous studies, which did not include effective content information. Then, based on 240 distribution sites of S. baicalensis and corresponding environmental variables via the MaxEnt method, we determined the distribution region of wild S. baicalensis . Next, a fuzzy matter element model was used to build the relationship between environmental variables and baicalin content. Finally, we integrated all the results to assess the habitat quality of the baicalin content in S. baicalensis across China. The results showed that compared with the genuine producing area of S. baicalensi, the high-quality habitats for a high baicalin content are further south. And the areas of habitat with high content of wild S. baicalensis based on baicalin in China were approximately 3.1 × 10 5 km 2 . The habitat of each category covered a large area in the distribution and the baicalin content differed from category to category obviously. Climatic factors wouldn't only be an indicator for identifying the potential distribution area, but also for forming some secondary metabolites such as baicalin. In conclusion, it is necessary to label the produce place of S. baicalensis plant when used as herbal medicine. Our results provide a reference for the establishment of S. baicalensi plantations .